2017
DOI: 10.18632/oncotarget.21010
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation plays a carcinogenic role through effector cytokine IL-18 in lymphoma

Abstract: Inflammasomes play important roles in the pathogenesis of tumors, but the roles of NLRP3 inflammasome in the lymphoma remain unclear. Activated NLRP3 inflammasome induces the maturation of its effector cytokine IL-18 which functions in the development of cancer. Here, we investigated the polymorphism and expression of NLRP3 inflammasome related genes and explored their function in lymphoma. We found that IL-18 (rs1946518) and NFκB94 ins/del (rs28362491) contributed to lymphoma susceptibility and allele G in IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 42 publications
1
49
0
1
Order By: Relevance
“…The nucleotide-binding oligomerization domain-like receptors (NOD-like receptors) family pyrin domain, containing 3 (NLRP3), is the most widely studied inflammasome. A previous study demonstrated that activated NLRP3 increases IL-18 in patients with lymphoma [ 55 ]. NLRP3 inflammasome could represent a novel potential target for the treatment of breast cancer [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide-binding oligomerization domain-like receptors (NOD-like receptors) family pyrin domain, containing 3 (NLRP3), is the most widely studied inflammasome. A previous study demonstrated that activated NLRP3 increases IL-18 in patients with lymphoma [ 55 ]. NLRP3 inflammasome could represent a novel potential target for the treatment of breast cancer [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have highlighted the role of individual inflammasome sensors in tumor proliferation and survival. NLRP3 activation in lymphoma cells produce IL-18 which attenuates dexamethasone-induced apoptosis 38 thereby promoting their survival (FIG. 2a).…”
Section: Inflammasome Activationmentioning
confidence: 99%
“…NACHT, LRR and PYD domains-containing protein 3 (NLRP3) is the most widely studied inflammasome. A previous study demonstrated that activated NLRP3 significantly promoted the protein expression level of IL-18 in the plasma of patients with lymphoma (6). Furthermore, it was identified that the activation of caspase-1 may trigger the maturation and secretion of IL-18 (7).…”
Section: Introductionmentioning
confidence: 97%